2014
DOI: 10.1128/jcm.00418-14
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimicrobial Susceptibility of Aerococcus urinae

Abstract: Aerococcus urinae may cause urinary tract infections, bacteremia, and endocarditis. No standardized susceptibility test methods or interpretive criteria have been proposed for this organism. This study reports the MIC results for 128 A. urinae isolates tested by broth microdilution. The isolates had low MICs to amoxicillin, cefotaxime, ceftriaxone, doxycycline, linezolid, meropenem, penicillin, rifampin, tetracycline, trimethoprim-sulfamethoxazole, and vancomycin. However, 55% of the isolates had MICs to clind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 21 publications
1
33
0
1
Order By: Relevance
“…In vitro, A. urinae is susceptible to amoxicillin, cefotaxime, ceftriaxone, doxycycline, linezolid, meropenem, penicillin, rifampin, trimethoprim-sulfamethoxazole, and vancomycin. It had variable resistance to clindamycin, erythromycin, and levofloxacin 5 . Several other studies have indicated that it is also resistant to sulfonamides and it may have variable resistance to vancomycin and trimethoprim-sulfamethoxazole 1 .…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, A. urinae is susceptible to amoxicillin, cefotaxime, ceftriaxone, doxycycline, linezolid, meropenem, penicillin, rifampin, trimethoprim-sulfamethoxazole, and vancomycin. It had variable resistance to clindamycin, erythromycin, and levofloxacin 5 . Several other studies have indicated that it is also resistant to sulfonamides and it may have variable resistance to vancomycin and trimethoprim-sulfamethoxazole 1 .…”
Section: Discussionmentioning
confidence: 99%
“…3 By broth microdilution, Humphries et al reported susceptibility rates of 84% for levofloxacin (LEV) and 97% for trimethoprim-sulfamethoxazole (SXT) using the Clinical Laboratory Standards Institute (CLSI) interpretive criteria. 4 As stated in a recent review by Rasmussen et al, the fosfomycin (FOS) susceptibility rate for A. urinae was 90% 1 ; however, these data were only based on twenty isolates. In an older study from 1997, which may not represent our current situation, Schuur et al reported that their collection of A. urinae was uniformly susceptible to nitrofurantoin (NIT).…”
Section: To the Editormentioning
confidence: 99%
“…1,3 However, using a broth microdilution MIC test with broth supplemented with 2.5% LHB, Humphries et al reported that most of their isolates were susceptible. 4 The thymidine present in conventional media is able to inhibit SXT. The addition of 2.5% LHB, however, modulates SXT susceptibility in that it provides endogenous thymidine phosphorylase which converts thymidine to thymine and thus restores the in vitro activity of the drug.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Les Aerococcus spp., sont sensibles aux glycopeptides, à la rifampicine, aux cyclines, au linézolide et à la gentamicine. Ils sont inconstamment sensibles aux macrolides [1,2,7,12]. Les études portant sur la sensibilité d'A.…”
Section: Résultatsunclassified